1997
DOI: 10.2527/1997.75123126x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genetic parameters for longissimus muscle fiber characteristics in relation to growth, carcass, and meat quality traits in large white pigs.

Abstract: A total of 383 barrows and gilts from a French Large White experimental herd were slaughtered at 100 kg BW. Samples of longissimus muscle were taken to categorize myofibers according to their contractile (I, IIA, and IIB) and metabolic (oxidative and nonoxidative) properties. Myofiber percentages, cross-sectional areas (CSA), and relative areas were measured. Growth rate, carcass composition, muscle chemical composition, metabolic enzyme activities, and meat quality traits were also measured to estimate phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

50
191
9
24

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 297 publications
(274 citation statements)
references
References 44 publications
50
191
9
24
Order By: Relevance
“…Average BF, FAT and PFAT of castrates were significantly higher than those of gilts (29.01 vs. 25.56 mm, 9.57 vs. 7.55 kg and 21.79 vs. 17.43%, respectively). The results are in agreement with previous reports on sex differences (Larzul et al, 1997;Tischendorf et al, 2002;Cassady et al, 2004). However, Mohrmann et al (2006) did not find any significant differences between the sexes (gilts and barrows), but gilts tended to have higher lean meat content.…”
Section: Resultssupporting
confidence: 83%
“…Average BF, FAT and PFAT of castrates were significantly higher than those of gilts (29.01 vs. 25.56 mm, 9.57 vs. 7.55 kg and 21.79 vs. 17.43%, respectively). The results are in agreement with previous reports on sex differences (Larzul et al, 1997;Tischendorf et al, 2002;Cassady et al, 2004). However, Mohrmann et al (2006) did not find any significant differences between the sexes (gilts and barrows), but gilts tended to have higher lean meat content.…”
Section: Resultssupporting
confidence: 83%
“…Contrary to most studies, they found that females had higher IMF content than castrates. In our study, castrates had higher IMF content than females; this was supported by Larzul et al (1997) and Bahelka et al (2007), who found significantly higher lean meat percentage and lower levels of IMF in females than in castrates. Latorre et al (2003) found significantly higher IMF content, and less moisture and protein in castrates than in females.…”
Section: Genetic Variation In Meat Qualitysupporting
confidence: 86%
“…Boars showed a higher diameter of muscle fibre type IIA (fast-twitch, oxido-glycolytic) and IIB (fasttwitch, glycolytic) than gilts. Conversely, Larzul et al (1997) found higher area of muscle fibre type IIB in gilts than boars. Also, Bee (2004) detected higher area of muscle fibre in m. semitendinosus in gilts.…”
Section: Introductionmentioning
confidence: 81%